Incoherent Cooper Pairing and Pseudogap Behavior in Single-Layer FeSe/SrTiO_{3} - B. D. Faeth (American Physical Society, 2021)
In many unconventional superconductors, the presence of a pseudogap—a suppression in the electronic density of states extending above the critical temperature—has been a long-standing mystery. Here, we employ combined in situ electrical transport and angle-resolved photoemission spectroscopy measurements to reveal an unprecedentedly large pseudogap regime in single-layer FeSe/SrTiO_{3}, an interfacial superconductor where incoherent Cooper pairs are initially formed above T_{Δ}≈60  K but where a zero-resistance state is achieved only below T_{0}<30  K. We show that this behavior is accompanied by distinct transport signatures of two-dimensional phase fluctuating superconductivity, suggesting a mixed vortex state hosting incoherent Cooper pairs which persist well above the maximum clean limit T_{c} of approximately 40 K. Our work establishes the critical role of reduced dimensionality in driving the complex interplay between Cooper pairing and phase coherence in two-dimensional high-T_{c} superconductors, providing a paradigm for understanding and engineering higher-T_{c} interfacial superconductors.